Cost-effectiveness of surgery for drug-resistant temporal lobe epilepsy in the US. (8th September 2020) - Sheikh, Shehryar R.; Kattan, Michael W.; Steinmetz, Michael; Singer, Mendel E.; Udeh, Belinda L.; Jehi, Lara
Abstract : Objective: Surgery is an effective but costly treatment for many patients with drug-resistant temporal lobe epilepsy (DR-TLE). We aim to evaluate whether, in the United States, surgery is cost-effective compared to medical management for patients deemed surgical candidates and whether surgical evaluation is cost-effective for patients with DR-TLE in general. Methods: We use a semi-Markov model to assess the cost-effectiveness of surgery and surgical evaluation over a lifetime horizon. We use second-order Monte Carlo simulations to conduct probabilistic sensitivity analyses to estimate variation in model output. We adopt both health care and societal perspectives, including direct health care costs (e.g., surgery, antiepileptic drugs) and indirect costs (e.g., lost earnings by patients and care providers.) We compare the incremental cost-effectiveness ratio to societal willingness to pay (∼100, 000 per quality-adjusted life-year [QALY]) to determine whether surgery is cost-effective. Results: Epilepsy surgery is cost-effective compared to medical management in surgically eligible patients by virtue of being cost-saving (328, 000 vs 423, 000) and more effective (16.6 vs 13.6 QALY) than medical management in the long run. Surgical evaluation is cost-effective in patients with DR-TLE even if the probability of being deemed a surgical candidate is only 5%. From a societal perspective, surgery becomes cost-effective within 3 years, and 89% of simulations favor surgery over the lifetime horizon. Conclusion: For surgically eligible patients with DR-TLE, surgery is cost-effective. For patients with DR-TLE in general, referral for surgical evaluation (and possible subsequent surgery) is cost-effective. Patients with DR-TLE should be referred for surgical evaluation without hesitation on cost-effectiveness grounds.